The Surrounded Atom Theory of Order-disorder Phase Transition in Binary Alloys - Ha, Do Chieu; Khanh, Nguyen Nhat (Communications in Physics, 2011)
In this paper, the surrounded atom model is developed to study the order-disorder phase transition in binary alloys. We calculate the configurational free energy of the alloys, derive the equation of equilibrium and determine the critical temperature of the phase transition.